PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA BERBASIS CTL PADA MATERI GERAK HARMONIK SEDERHANA - Wijaya, Fisa Wisnu; Taufiqqurachman, Taufiqqurachman; Sutisna , Moch Arief (EduFisika: Jurnal Pendidikan Fisika, 2022)
This development research aims to produce a valid and reliable Contextual Teaching Learning-based performance appraisal tool. The development design uses ADDIE (Analyze, Design, Develop, Implementation, and Evaluation). The performance appraisal step is carried out in 4 stages, namely 1) the preparation stage: determining competence, determining scoring guidelines, adjusting teaching materials, making instrument grids and making assessment items, 2) Implementation stages: conducting expert validation tests and field tests) 3) Stages scoring 4) Reporting stage. The results showed that the Contextual Teaching Learning-based performance appraisal instrument which was validated by instrument experts obtained a total result of 85.7% with a very good category. The results of the field test by 33 students of class X MA AL Aisyah showed very high validity and reliability and obtained 31 valid items and 4 items were declared invalid. The value of rtable = 0.361 with a significance level of 5% validity test using Cronbach's alpha obtained rcount = 0.89 this proves that the instrument is in the high category. So that the Contextual Teaching Learning-based performance assessment instrument on simple harmonic motion material is feasible to use.Â